VARIASI LAMA PERENDAMAN DENGAN LARUTAN EKSTRAK NANAS (ANANAS COMOSUS L. MERR) TERHADAP SUSUT MASAK DAN UJI ORGANOLEPTIK DAGING AYAM PETELUR AFKIR - Danang Biyatmoko; Sugiarti .; Abrani Sulaiman (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
The aim of the study was to determine the effect of soaking time with pineapple extracts on cooking shrinkage and organoleptic test on the meat of rejected laying hens. The method used was Completely Randomized Design (CRD) with five treatments and four replications, the treatment given was a different immersion time, P0 (without soaking pineapple fruit extract), P1 (soaked with 250 ml pineapple fruit extract for 30 minutes), P2 (soaked with 250 ml pineapple fruit extract for 60 minutes), P3 (soaked with 250 ml pineapple fruit extract for 90 minutes), P4 (soaked with 250 ml pineapple fruit extract for 120 minutes). Variables measured are cooking shrinkage and organoleptic (color, flavor, tenderness and flavor). Data analyzed on cooking shrinkage using analysis of variance (ANOVA), if analyzed significantly, it will be continued with a mean difference test using the Duncan's Multiple Region Test (DMRT) while the non parametic organoleptic test will be tested using Kruskall Wallis test. The results showed that the effect of soaking meat of culled laying hens with the use of pineapple extract solution can increase the cooking shrinkage provides highly significant effect (P˂0,01) against the meat of laying hens culled and able to improve the organoleptic meat of culled laying hens which provide different influences real (P˂0,05). The average of organoleptic test with soaking laying hens with the use of pineapple extract solution which was given the best treatment was achieved in P4 treatment. Keywords: soaking time, pineapple extract, rejected laying hens, cooking shrinkage, organoleptic test.